The contribution of leg muscle power and eye-foot coordination to the accuracy of futsal shooting of students - Imka, A. J.; Jatra, R.; Dafun JR, P. B. (Journal of Applied Movement and Sport Science, 2025)
Background Shooting accuracy is a fundamental skill in futsal, yet preliminary observations at State Junior High School 35 Pekanbaru showed that students still demonstrate low shooting performance, indicated by weak ball power, inaccurate ball direction, and poor foot-ball contact. These symptoms suggest inadequate leg muscle power and insufficient eye-foot coordination, which may inhibit students` ability to perform accurate shots.